Magnitude and associated factors of unmet need for family planning among rural women in Ethiopia: a multilevel cross-sectional analysis - Adugnaw Zeleke Alem (BMJ Open)
Objective This study was aimed to assess the magnitude and associated factors of unmet need for family planning among rural women in Ethiopia.Design Cross-sectional study.Setting Ethiopia.Participants Reproductive age group women.Primary outcome Unmet need for family planning.Methods This study drew data from Ethiopian Demographic and Health Survey, which was conducted from 18 January to 27 June 2016. A total of 8327 rural reproductive-aged (15–49 years) women were included. A two-level multivariable logistic regression model was carried out to identify individual and community-level factors associated with unmet need for family planning. Adjusted OR (AOR) with a 95% CI was used to assess the strength of association between independent and dependent variables.Results The overall unmet need for family planning among rural women was 24.08% (95% CI 23.17 to 25.01), of which 14.79% was for spacing and 9.29% for limiting. Number of children (AOR=1.15; 95% CI 1.07 to 1.24) and working status of women (AOR=1.18; 95% CI 1.02 to 1.37) were significantly associated with a higher odds of unmet need for family planning. However, women with primary education (AOR=0.87; 95% CI 0.74 to 0.94), women married at age 18 or later (AOR=0.82; 95% CI 0.70 to 0.96), women from households with high wealth index (AOR=0.77; 95% CI 0.64 to 0.94), women who deem distance to a health facility as not a big problem (AOR=0.85; 95% CI 0.73 to 0.99), women from communities with a high percentage of educated women (AOR=0.73; 95% CI 0.59 to 0.89) and women who live in communities with high media exposure (AOR=0.81, 95% CI 0.68 to 0.98) were significantly associated with a lower odds of unmet needs for family planning.Conclusion Unmet need for family planning among reproductive-aged women in rural Ethiopia was high. Number of children, working status of women, women’s education, age at first marriage, household wealth, distance to a health facility, community women’s education and community media exposure were significantly associated with unmet needs for family planning. Therefore, to reduce unmet need for family planning, public health policymakers should consider both individual and community-level factors when designing FP programmes and emphasis should be given to high-risk populations.